CeO2-Based Two-Dimensional Layered Nanocomposites Derived from a Metal–Organic Framework for Selective Electrochemical Dopamine Sensors - Chengjie Ge; Rajendran Ramachandran; Fei Wang (Sensors, 2020)
In this work, we demonstrate the incorporation of two-dimensional (2D) layered materials into a metal–organic framework (MOF) derived from one-dimensional (1D) cerium oxide (CeO2) for the electrochemical detection of dopamine. Ce-MOF was employed as a sacrificial template for preparing CeO2 with 2D materials by the pyrolysis process. The influence of the pyrolysis temperature was studied to achieve a better crystal structure of CeO2. Siloxene improved the dopamine sensing performance of CeO2 compared with graphitic carbon nitride (g-C3N4) due to the basal plane surface oxygen and hydroxyl groups of 2D siloxene. Under optimal conditions, the fabricated CeO2/siloxene electrode exhibited a detection limit of 0.292 μM, with a linear range from 0.292 μM to 7.8 μM. This work provides a novel scheme for designing the CeO2 material with siloxene for excellent dopamine sensors, which could be extended towards other biosensing applications.